A model for the optimization of anti-inflammatory treatment with chemerin. Issue 1 (6th February 2018) - Laranjeira, Simao; Regan-Komito, Daniel; Iqbal, Asif J.; Greaves, David R.; Payne, Stephen J.; Orlowski, Piotr
Abstract : Routine treatment of mild to moderate pain with a combination of non-steroidal anti-inflammatory drugs such as paracetamol in combination with corticoid opioids can lead to severe complications including death from gastrointestinal injury or to drug dependence. There is a need for the development of new safer drugs. Chemerin is a mediator promoting resolution of inflammation and it is then a promising candidate for a new treatment. A pilot experimental work using the zymosan-induced peritonitis model has found that injecting extra chemerin resulted in an approximately 1% reduction in the total number of inflammatory cells recruited. This paper combines and adapts existing mathematical models of inflammation to reproduce these results and to explore the therapeutic potential of chemerin through simulations. Analysis of the model predicts that the injection of chemerin at a concentration of 2000 ng ml −1 within the first 5 min of inflammation onset leads to maximal inflammation inhibition. The degree of inhibition is shown to be sensitive to data used for the fit with a mean inhibition of 22 ± 3.7% for a series of remove-one bootstrap tests, whereas optimal chemerin injection parameters were not. Overall sensitivity analysis identifies parameters of the model that need to be measured more accurately or with increased sampling rate to improve model robustness and confirm chemerin's therapeutic potential.